IMPLEMENTASI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERKAIT DENGAN KEBEBASAN BERPENDAPAT DALAM PERSPEKTIF HAK ASASI MANUSIA - Mahendar Nasution, Muhammad Rafi; Marlina, Marlina; Akhyar, Adil (Jurnal Ilmiah METADATA, 2021)
The presence of social networks brings changes in communication. So that when people communicate in social networks, they must have good and correct ethics in interacting with other people, because mistakes in interacting result in criminal sanctions. The problems in this discussion are how to regulate the expression of opinions through social media according to the ITE Law, how to apply ITE in relation to the basic right of every citizen to express freedom of opinion, whether criminal acts or offenses in the provisions of the ITE Law can be applied to citizens. people who express opinions or criticize the government. This study uses a descriptive method through a normative approach (legal research), namely an approach to problems, carried out by examining various legal aspects in terms of applicable regulations. The results show that the regulation on expressing opinions through social media according to the ITE Law has been clearly regulated and guaranteed in various legal instruments in Indonesia, such as the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 concerning Human Rights, Law Number 9 of 1999. 1998 concerning Freedom to Express Opinions in Public, Law Number 14 of 2008 concerning Disclosure of Public Information and Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The application of ITE in relation to the basic right of every citizen to express freedom of opinion cannot be reduced or limited by anyone and by anything. Criminal acts or offenses in the provisions of the ITE Law can be applied to citizens who express opinions or criticisms of the government, if the actions meet the elements of criminal acts as stipulated in the ITE Law, then the perpetrators can be subject to sanctions or must be held accountable for their actions.